Algoritma Goal Programming untuk Driver Assignmentpada Simulasi Taksi Online - Lienny Ferlinda; Andreas Handojo; Tanti Octavia (Jurnal Infra, 2022)
Taxi is one of the most common means of public transportation. Assignment of drivers to passengers in online taxi can be done by of ering passenger orders to all drivers closest to the pick-up location. This method has high time ef iciency. However, this causes an increase in the cancellation rate because drivers don't have enough time to view order details, just as long as they accept orders. This can lead to a decrease in the level of passenger satisfaction and online taxi revenue. Therefore, other factors such as driver rating, driver order cancellation rate, number of orderscompleted by drivers are important to consider in the assignment process to produce an ef icient assignment. The process of assigning drivers and passengers will be carriedout using the Goal Programming method because this methodissuitable for problems in decision making that involve morethanone goal (multi-objectives). The results showed that Goal Programming resultedinthehighest total calculation time. In addition, the average waitingtime for passengers and pick-up distance are the lowest. TheHungarian Algorithm method has a faster calculationtimecompared to the Goal Programming method, however, thenumber of assignment is lower. In addition, the average waitingtime for passengers and their pick-up distances is higher. TheRandom Assignment method has the fastest calculation timeandthe highest assignment success rate. However, the averagewaiting time for passengers and the distance to pick themupisfarabove the two comparison methods. The addition of factors otherthan time and pick-up distance in a low percentage can af ect theaverage value of these factors for the better. But, the averagepick-up time and distance is increasing.